Hubungan Pola Asuh Ibu dengan Perilaku Sulit Makan pada Anak Usia Prasekolah - Listiana, Devi; Colin, Vellyza; Syndita, Lidya (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2020)
Difficulty eating behavior can lead to nutritional problems in children, where children who have difficulty eating tend to experience malnutrition to malnutrition. This study aims to determine the relationship between mother's upbringing and eating difficult behavior in preschool children in RW. 002 Kelurahan Sidomulyo Bengkulu City. The method used in this research is the correlational method. The population in this study were all mothers who have children at preschool age. The sampling technique used in this study was accidental sampling of 59 respondents. The data used are primary data and secondary data. Data were analyzed using univariate analysis and bivariate analysis. The results obtained from 59 respondents, there were 52 (88.1%) respondents with good parenting, 49 respondents (83.1%) did not experience difficult eating behavior. The results of the Pearson Product Moment correlation analysis obtained p value = 0.419. In conclusion, there is no relationship between mother's upbringing and eating difficult behavior among preschool children in RW. 002 Kelurahan Sidomulyo Bengkulu City. Health workers are expected to be able to provide information and input for mothers with preschool children about eating difficult behaviors to prevent and overcome eating difficult behavior in children.Â Key words: preschool age, difficult eating behavior, mother's parenting